Volumetric enhancement of Raman scattering for fast detection based on a silver-lined hollow-core fiber - Chu, Qian (2019)
Fast detection and identification of chemicals are of utmost importance for field testing and real-time monitoring in many fields. Raman spectroscopy is the predominant technique in principle, but its wide application is limited on account of weak scattering efficiency. Surface Enhanced Raman Spectroscopy (SERS) technique provides a solution for signal enhancement, but may not good at fast detection due to cross contamination and bulky instruments. Hollow-core fiber-based Raman cell with long interaction length can achieve high detection sensitivity, but it also suffers from low flow rate, bulky high-pressure equipment and light coupling structure, which also restricts its application for fast detection. In order to solve those problems, we proposed a portable Raman cell, by using metal-lined hollow-core fibers (MLHCF) with large bandwidth, good field confinement, extremely large numerical aperture and arbitrary length. With our proposed fiber inserted light coupling and light reflecting method, a Raman cell of 3.1 cm in length provides nearly 50 times of signal enhancement compared with direct detection using bare fiber tip. Furthermore, the sample exchange rate could be as fast as 1 second even under normal pressure without any cross contamination. At last, we also demonstrated the underlying general mechanism of signal enhancement and summarized it as volumetric enhancement of Raman scattering (VERS). Both the experiment results and the theoretical analysis demonstrated that our device has the potential for fast online Raman detection, which also possesses high-sensitivity and high-accuracy.